REFORMATION OF ISLAMIC EDUCATIONAL INSTITUTIONS IN ACEH (STUDY OF MADRASAHS IN 1915-1946) - Muslim, Muslim; Mukti, Abd; Arsyad, Junaidi (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to analyze the dynamics of the renewal of Islamic educational institutions in Aceh in the period 1915-1946. The focus of the study lies on the emergence and development of madrasahs as a form of transformation of Islamic education from a traditional system to a modern model that is more relevant to the needs of the times. By using the approach of social institutional theory and modernization theory, this study explains the role of madrasahs in improving access to education, teaching quality, and contributions to Acehnese society. The research method used is a historical study, which includes four stages: heuristics, criticism, interpretation, and historiography. Data were obtained from primary sources such as archives, colonial documents, works of scholars, and physical artifacts of madrasah buildings. The criticism process was carried out to ensure the validity, objectivity, and relevance of the data. Interpretative analysis was used to understand the social, political, cultural, and religious influences on the development of madrasahs in Aceh. The results of the study show that the renewal of Islamic education in Aceh encouraged the development of madrasahs as educational institutions that not only teach religious knowledge but also general knowledge. This renewal improves the quality of madrasah graduates who are able to contribute as scholars, educators, community leaders, and government officials. In addition, madrasas expanded access to Islamic education to remote areas, including for women, and played an important role in maintaining the religious and cultural identity of the Acehnese people amidst the pressures of colonialism.